Prevalence of Gastro-Intestinal Parasites of Horse (Equus Caballus Linnaeus, 1758) In Seven Village Development Committee of Rukum District, Nepal - Oli, Naresh; Subedi, Janak Raj (Journal of Institute of Science and Technology, 2018)
This study aimed to determine the prevalence of gastro-intestinal parasites of horse in seven Village Development Committee (VDC) of Rukum district. It was carried out from March to November 2016. A total of 105 fecal samples of horses (79 males and 26 females) were collected by using opportunistic random method. The collected fecal samples were preserved in 2.5% potassium dichromate and microscopically examined using concentration techniques. The overall prevalence of gastro-intestinal parasites was 84.76% (89/105). The total number of genera observed during fecal examination was 12. Among them, Strongylus sp. showed the highest prevalence (51.42%) followed by Eimeria sp. (20%), Trichostrongylus sp. (14.28%), Trichonema sp. (13.33%), Parascaris equorum (10.47%), Balantidium sp. (9.52%), Dictyocaulus sp. (8.57%), Triodontophorus sp. (7.61%), Gastrodiscus sp. (6.66%), Oxyuris equi (4.76%), Entamoeba sp. (3.80%), Shistosoma sp. (1.90%) and unidentified nematode larvae (7.61%). Three genera of parasites; Shistosoma sp., Triodontophorus sp. and Dictyocaulus sp. have been reported for the first time in horses of Nepal. Present study showed higher infection rate in females (92.30%) than in male horses (82.27%). No significant association was observed between the prevalence of parasite rate with VDC (χ2 = 5.7161; p>0.05) and sex of animals (χ2 = 0.3346; p>0.05). Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 70-75